Sweet Taste Is Complex: Signaling Cascades and Circuits Involved in Sweet Sensation - von Molitor, Elena; Riedel, Katja; Krohn, Michael; Hafner, Mathias; Rudolf, Rüdiger; Cesetti, Tiziana (Frontiers in Human Neuroscience, 2021)
Sweetness is the preferred taste of humans and many animals, likely because sugars are a primary source of energy. In mammals, sweet compounds are sensed in the tongue by the gustatory organ, the taste buds. Here, a group of taste-bud cells expresses a canonical sweet-taste receptor, whose activation induces Ca2+ rise, cell depolarization and ATP release to communicate with afferent gustatory nerves. The discovery of the sweet-taste receptor, 20 years ago, was a milestone in the understanding of sweet signal transduction and is described here from a historical perspective. Our review briefly summarizes the major findings of the canonical sweet taste pathway, and then focuses on molecular details, about the related downstream signaling, that are still elusive or have been neglected. In this context, we discuss evidence supporting the existence of an alternative pathway, independent of the sweet-taste receptor, to sense sugars and its proposed role in glucose homeostasis. Further, given that sweet-taste receptor expression has been reported in many other organs, the physiological role of these extraoral receptors is addressed. Finally, and along these lines, we expand on the multiple direct and indirect effects of sugars on the brain. In summary, the review tries to stimulate a comprehensive understanding of how sweet compounds signal to the brain upon taste-bud cells activation, and how this gustatory process is integrated with gastro-intestinal sugar sensing to create a hedonic and metabolic representation of sugars, which finally drives our behaviour. Understanding of this compley networks is indeed a crucial step in developing new strategies to prevent obesity and associated diseases.